2014
DOI: 10.1111/jedm.12057
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced Approach to Combine Item Response Theory With Cognitive Diagnosis in Adaptive Testing

Abstract: Computerized adaptive testing offers the possibility of gaining information on both the overall ability and cognitive profile in a single assessment administration. Some algorithms aiming for these dual purposes have been proposed, including the shadow test approach, the dual information method (DIM), and the constraint weighted method. The current study proposed two new methods, aggregate ranked information index (ARI) and aggregate standardized information index (ASI), which appropriately addressed the nonco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 37 publications
1
40
0
2
Order By: Relevance
“…Later, Wang et al. () proposed transformation of the two information pieces into the ordinal scale and standardized scale. Each criterion was named as the aggregate ranked information (ARI) index and the aggregate standardized information (ASI) index.…”
Section: Item Selection Based On Kl Informationmentioning
confidence: 99%
See 3 more Smart Citations
“…Later, Wang et al. () proposed transformation of the two information pieces into the ordinal scale and standardized scale. Each criterion was named as the aggregate ranked information (ARI) index and the aggregate standardized information (ASI) index.…”
Section: Item Selection Based On Kl Informationmentioning
confidence: 99%
“…After obtaining the response data sets, we retrofitted the generating CDM and the two‐parameter logistic model (2PLM) based on marginal maximum likelihood estimation with the expectation‐maximization algorithm (Bock & Aitkin, ; de la Torre, ) similar to Wang et al. ().…”
Section: Simulation Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Makransky et al (2013), for example, showed how MAT can be used with polytomous items. Other papers have focused on employing complex model structures in MAT (Huang et al, 2012; Wang, 2014; Wang et al, 2014; Mikolajetz and Frey, in press), on MAT with exposure control (Lee et al, 2008; Diao et al, 2009; Finkelman et al, 2009), on the simultaneous consideration of multiple restrictions in MAT (Veldkamp and van der Linden, 2002; Su, 2016; Born and Frey, in press), on online calibration (Chen and Wang, 2016) and on comparing different item selection methods for composite scores and sub scores in general (Yao, 2012), with respect to different test termination criteria (Yao, 2013), and different exposure control and content managing methods (Yao, 2014). …”
Section: Introductionmentioning
confidence: 99%